Piauí Regional Gastronomy: a Tool for Cultural - Araújo, Antônia Beatriz Ribeiro (2022)
Gastronomy can be considered a key aspect of an intangible cultural asset and is included in the Livro de Registro dos Saberes (Knowledge Record Book) of the Instituto do Patrimônio Histórico e Artístico Nacional (National Historic and Artistic Heritage Institute) in Brazil. Brazilian gastronomic traditions are considered as a large set of socio-cultural practices and in simple dishes, food and production habits from many generations are attributed. In this way, the aspects of identity inherent to social transitions between communities, generating the feeling of belonging among social groups, which until then saw these habits as a simple means of subsistence, are currently an attraction of great influence in the tourist, cultural and geographical field. Thus, this research aimed to recognize from the point of view of gastronomy the expertise of making cassava flour as an intangible cultural heritage of the state of Piauí, being a relevant activity for the subsistence of many communities such as the village of Canto Grande, in the municipality of Cajueiro da Praia, in the state of Piauí. The methodology adopted was based on bibliographic research in books and scientific articles, in addition to participatory observation, in the context of the production processes of the cassava flour in the village of Canto Grande, providing information about the diversified method of production and the materials and tools used by this community located in the northern part of Piauí.